2013
DOI: 10.1002/cae.21590
|View full text |Cite
|
Sign up to set email alerts
|

Interactive learning management system to develop spatial visualization abilities

Abstract: An Interactive Learning Management System (ILMS) is presented, which functions as a webbased Spatial Visualization Ability (SVA) learning support tool for students of engineering graphics and as a management tool for teachers to track student learning. This software is designed to fill the gaps in student knowledge, giving them more uniform spatial visualization abilities when enrolling on University Engineering degrees. The ILMS_SVA consists of: 1) a Content Management System (CMS); 2) a preliminary level ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…15 Paired t-Test (2-tailed) for all tested groups of Computer Graphics was reached after obtaining a strong measure in the paired t-test which supported the alternative hypothesis that the mean difference between the pre-test and post-test phases was statistically significant. This finding confirms the expected results, considering that previous works of literature indicated that VSA could be reinforced or trained through specially designed cognitive exercises (Crown, 2001;Melgosa Pedrosa et al, 2015;Friess et al, 2016;Gerson et al, 2001;Martín-Dorta et al, 2008;Sorby, 2009). In this study, despite the fact that students did not perform or participate in any specially designed activity, it seems that just the regular course work in CG was enough to increase their performance on the PSVT.…”
Section: Discussionsupporting
confidence: 91%
“…15 Paired t-Test (2-tailed) for all tested groups of Computer Graphics was reached after obtaining a strong measure in the paired t-test which supported the alternative hypothesis that the mean difference between the pre-test and post-test phases was statistically significant. This finding confirms the expected results, considering that previous works of literature indicated that VSA could be reinforced or trained through specially designed cognitive exercises (Crown, 2001;Melgosa Pedrosa et al, 2015;Friess et al, 2016;Gerson et al, 2001;Martín-Dorta et al, 2008;Sorby, 2009). In this study, despite the fact that students did not perform or participate in any specially designed activity, it seems that just the regular course work in CG was enough to increase their performance on the PSVT.…”
Section: Discussionsupporting
confidence: 91%
“…(Alvarez et al, 2017;Martín-Gutiérrez y González, 2016;Šafhalter et al, 2020Šafhalter et al, y Samsudin et al, 2011 todos ellos efectivos siempre y cuando las actividades diseñadas sean específicas del contexto (Mohler, 2006). Sin embargo, en los últimos 20 años dado el avance de la tecnología, se han creado diversos entrenamientos basados en tecnologías atractivas para los estudiantes (Roca-González et al, 2017), entrenamientos utilizando software de modelado 3D (Torner et al, 2015), usando archivos 3D-PDF, (Gómez-Tone, 2019), desarrollo de un Sistema de Gestión de Aprendizaje Interactivo para desarrollar la capacidad de visualización espacial (Melgosa Pedrosa et al, 2015), formación basada en realidad virtual, herramientas interactivas y formación en exteriores (Gómez-Tone et al, 2020, Martin-Gutiérrez et al, 2013y Roca-Gonzalez et al, 2014 A pesar del enorme avance del conocimiento de las habilidades espaciales y su entrenamiento, en Latinoamérica, y en concreto en el Perú, no se ha dado la importancia necesaria a la evaluación y desarrollo de la Capacidad Espacial en la educación superior. Sucede entonces, que en el primer año los estudiantes de ingeniería con mayor Capacidad Espacial obtienen mayor calificación en las asignaturas de Ingeniería Gráfica (Arrieta y Medrano, 2015) y, en general, en los demás cursos como el Cálculo, Física o Química, mientras que los estudiantes con un desarrollo incipiente de dichas capacidades tienen gran desventaja al afrontar tales asignaturas (Acevedo et al, 2015) y por su puesto en la asignatura de expresión gráfica (S. A.…”
Section: Entrenamiento De Habilidades Espacialesunclassified
“…Consequently, the Spanish Ministry of Science and Innovation (currently the Ministry of Universities) has ensured that the development of spatial skills in engineering students is explicitly mentioned in the official regulations governing engineering curricula [15]. In Spain, the task of improving engineering students' spatial abilities has been addressed using training sessions employing technologies that have proven to be attractive to students [16], i.e., 3D solid modelling software [17]; the development of an interactive learning management system to develop spatial visualization skills [18]; or virtual reality-based training, interactive tools, and outdoor training [16,19].…”
Section: Introductionmentioning
confidence: 99%